Blood versus crystalloid cardioplegia for pediatric cardiac surgery: a meta-analysis. (October 2015) - Fang, Y; Long, C; Lou, S; Guan, Y; Fu, Z
Objective: Blood and crystalloid cardioplegia are the main myocardial protective solutions used in pediatric cardiac surgery. However, the effectiveness of these two solutions on myocardial metabolism, reperfusion injury and clinical outcomes in pediatric patients is still under debate. The purpose of this meta-analysis was to compare the efficacy of these two cardioplegia solutions in pediatric cardiac surgery. Methods: Keyword searches were performed on PUBMED, EMBASE and The Cochrane Library for randomized, controlled, clinical studies which were primarily comparing blood and crystalloid cardioplegia in pediatric cardiac surgery and provided data of postoperative cardiac troponin I (cTnI), lactate, mechanical ventilation time, length of intensive care unit (ICU) stay and inotropic support. Databases were searched from 1966 to June 2013 and were restricted to peer-reviewed English language publications of human subjects. We summarized the combined results of the data as mean difference (MD, when outcome measurements were made on the same scale) or standard mean difference (SMD, when the studies assess the same outcome with different scales), with 95% confidence intervals. Results: Five studies were identified, with a total of 323 patients. Lactate level after cardiopulmonary bypass (CPB) was significantly lower after blood cardioplegia compared with crystalloid cardioplegia (SMD 1.09, 95%CI 0.12 to 2.06, p=0.03); cTnI release postoperatively at 4-6 h (MD 0.92 ng/ml, 95%CI -0.13 to 1.97, p=0.09), 12 h (MD 0.2 ng/ml, 95% CI -0.43 to 0.84, p=0.53) and 24 h (MD 0.98 ng/ml, 95%CI -0.26 to 2.22, p=0.12) was not significantly different between the groups; ventilation duration (MD 5.15 hours, 95%CI -7.51 to 17.81, p=0.42) and length of ICU stay (SMD -0.3, 95%CI -0.80 to 0.21, p=0.25) were not significantly different between the groups either. Conclusion: Myocardial metabolism was better in the blood cardioplegia group compared with the crystalloid cardioplegia group. However, there was no evidence of improvement in myocardial damage or clinical outcome for either cardioplegia solution.